The State of the World's Children 2016 - United Nations Children's Fund (United Nations, 2016)
The State of the World’s Children 2016, a UNICEF flagship report, argues that progress for the most disadvantaged children and families is the defining condition for delivering on the 2030 Sustainable Development Goals. Millions of children’s lives around the world are blighted for no reason other than the country, gender or circumstances into which they are born. Failure to reach them now will fuel intergenerational cycles of disadvantage that will imperil their future and the future of the world.We have a clear choice to make: Invest in accelerated progress for the children being left behind, or face the consequences of a far more divided and unfair world by 2030.